KEPATUHAN PERUSAHAAN GO-PUBLIK INDONESIA PADA CODE OF GOOD CORPORATE GOVERNANCE - Thiasel, Clarisa; Ashakur, Farhan Kesar; Zaitul, Zaitul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The purpose of this study is to evaluate the extent to which public companies in Indonesia comply with the principles of Good Corporate Governance (GCG) in accordance with the provisions of POJK No.55/POJK.04/2015 and POJK No.33/POJK.04/2014. The implementation of GCG is considered crucial in encouraging transparency, accountability, and improving company performance, while strengthening the trust of investors and other stakeholders. This study specifically highlights two key elements of GCG, namely the existence of an Independent Board of Commissioners and the effectiveness of the work of the Independent Audit Committee, as well as how these two aspects affect the company's Return on Assets (ROA) and share price. The research approach is normative with a literature study method, which utilizes secondary data in the form of annual reports from 30 companies listed on the Indonesia Stock Exchange in 2024. The findings show that all samples have met the minimum provisions of the 30% proportion of Independent Commissioners according to regulations. However, there are differences in terms of the background and capabilities of the members of the Audit Committee, which have an impact on the quality of supervision and the reliability of financial statements. Companies that use the services of Public Accounting Firms (KAPs) from the "Big Four" group tend to show higher stability in ROA and stock prices, reflecting a more positive market valuation. The study also found a positive relationship between compliance with GCG principles and operational efficiency and stock price stability, which is in line with agency theory and signaling. Therefore, this study recommends improving the quality of supervision and audit competence to reduce the potential for fraud and strengthen the competitiveness of companies in the capital market.